The effect of physical activity programs on improving motor, social and attitude abilities of students with autism spectrum disorders in inclusive schools - Viorella, Nanda; Islamia, Siska Fedina; Ramdani, Robitul Umam; Istianatusyahri, Dewi; Novianti, Ranti (Universitas Ahmad Dahlan, 2024)
Children with Autism Spectrum Disorder (ASD) often experience motor skill challenges attributed to low muscle tone, impaired postural control, motor planning deficits, and impaired coordination. These difficulties can impede their participation in their surroundings, affecting their attitudes and social interactions. Physical activity programs serve as a method not only to enhance the physical abilities of students with ASD but also to mitigate inappropriate behaviors and foster social skills. The participant in this study was a 12-year-old child with mild autism attending Anak Saleh Inclusive Elementary School in Malang City. The study aims to investigate the impact of a physical activity program on improving motor, social, and attitudinal skills among children with autism spectrum disorder in an inclusive school setting. Data collection involved command tests including throwing a ball, kicking a ball, and jumping, each of which was assigned a score. The research utilized a Single Subject Research (SSR) experimental method with an A-B design, and descriptive statistical techniques were employed for data analysis. The results revealed a significant effect of the physical motor activity program on enhancing the motor, social, and attitudinal abilities of autistic students, particularly evident in improved social interaction and physical capabilities such as recognizing emotions and increasing hand and foot muscle strength. However, it's important to note that the findings of this study may not be generalizable to all ASD students due to the limited sample size. Nonetheless, this study contributes to the advancement of intervention methods for children with autism.